2018
DOI: 10.11604/pamj.2018.29.24.12276
|View full text |Cite
|
Sign up to set email alerts
|

Connaissances et comportements de 50 familles congolaises concernées par la drépanocytose: une enquête locale

Abstract: IntroductionLa drépanocytose est très fréquente en République Démocratique du Congo (RDC). Cette étude évalue le niveau de connaissance et les comportements de familles concernées ainsi que l’impact de cette maladie dans leur quotidien.MéthodesC’est une étude transversale, sur un échantillon non aléatoire, menée du 15 juin au 15 août 2015 auprès de 50 familles concernées par la drépanocytose à Mbujimayi en RDC.RésultatsSur 50 familles étudiées, 22 familles avaient plus d’un enfant drépanocytaire. L’âge médian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
5
6
0
4
Order By: Relevance
“…The results of the first year of follow-up showed that sickle cell children without any specific medical intervention presented severe clinical and hematological pictures with an annual average of four VOCs, four infectious episodes, one acute thoracic syndrome, and four hospitalizations, demonstrating the severity of the disease in a remote area of a developing country. Annual averages of acute events and degradation of biological parameters similar to the results of this study among SCD patients who have not been followed-up with in the past have been reported in the literature [47,50,[53][54][55]; however, there were no reports on the impact of regular follow-ups in those studies.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the first year of follow-up showed that sickle cell children without any specific medical intervention presented severe clinical and hematological pictures with an annual average of four VOCs, four infectious episodes, one acute thoracic syndrome, and four hospitalizations, demonstrating the severity of the disease in a remote area of a developing country. Annual averages of acute events and degradation of biological parameters similar to the results of this study among SCD patients who have not been followed-up with in the past have been reported in the literature [47,50,[53][54][55]; however, there were no reports on the impact of regular follow-ups in those studies.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the first year of follow-up showed that sickle cell children without any specific medical intervention presented severe clinical and hematological pictures with an annual average of 4 VOCs, 4 infectious episodes, 1 acute thoracic syndrome, 4 hospitalizations demonstrating the severity of the disease in a remote area of a developing country. Annual averages of acute events and degradation of biological parameters similar to the results of this study among SCD patients who have not been followed-up in the past were reported in the literature [47,50,[53][54][55]; however, those studies did not report the impact of a regular follow-up.…”
Section: Discussionsupporting
confidence: 83%
“…Mais en rapport avec le sexe, les études sont contradictoires. Certaines montrent une prédominance masculine [28, 29]; d'autres une prédominance féminine [29-32]; d'autres encore une répartition égale entre les 2 sexes [33, 34]. Nous pensons que la prédominance de l'un ou l'autre genre est le fait du hasard.…”
Section: Discussionunclassified